2021
DOI: 10.1177/08927057211057113
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyoxymethylene/methyl vinyl silicone rubber/thermoplastic polyurethane ternary thermoplastics vulcanizates with good toughness properties

Abstract: Novel thermoplastic vulcanizates (TPVs) based on polyoxymethylene (POM) and methyl vinyl silicone rubber (MVQ) have been prepared by dynamic vulcanization process through a batch mixer. During the preparation of TPV blends, Di-(tert butyl peroxyisopropyl) benzene (BIBP) was used as the curing agent in order to make MVQ cross-linked and TPU was used to coat MVQ for improving the compatibility of MVQ and POM. In order to understand the influence of different compositions on TPV blends, five groups of experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…1 Due to their distinctive properties, these materials are generally used as a matrix in the composites depending on the desired requirements. [2][3][4][5][6][7][8][9][10][11] For instance, Ma et al 2 performed tensile and endnotched flexure tests to examine the failure behaviour and mechanical properties of the thermoset and thermoplastic composites. As a result, the damage was observed in the interfacial fracture mode for the thermoplastic composites with the weak interface but high Mode II interlaminar fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to their distinctive properties, these materials are generally used as a matrix in the composites depending on the desired requirements. [2][3][4][5][6][7][8][9][10][11] For instance, Ma et al 2 performed tensile and endnotched flexure tests to examine the failure behaviour and mechanical properties of the thermoset and thermoplastic composites. As a result, the damage was observed in the interfacial fracture mode for the thermoplastic composites with the weak interface but high Mode II interlaminar fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The toughening of POM by incorporating elastomers was reported in many studies. [9][10][11][12] Pan et al [13] reported a 250% and 334% increase in impact resistance and tensile strain of POM/ABS (80/20), as compared to neat POM. The tensile strength was, however, decreased about 40% with ABS inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the substituting of fluorine provides to improving in the thermal stability by reducing flammability, decreasing of the surface energy and friction coefficient as well as increasing the electrical and optical features. 14 However, the compatibility level between the components, which is the main factor affecting directly the properties (especially mechanical) of the matrix, 15,16 becomes relatively lower in the composites including the fluoropolymers when compared to the others. In order to get rid of such adhesion problem, the polymer filler obtained from the fluoroalkyl acrylates (FAs) can be used in the composites.…”
Section: Introductionmentioning
confidence: 99%